2020
DOI: 10.4028/www.scientific.net/kem.854.194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Total Surface Area of Nanopores of Leningrad Deposits Oil Shale

Abstract: The article is devoted to the analysis of the influence of heat treatment of oil shale of the Leningrad field on the total surface area of nanopores and total porosity. Oil shale with particle size up to 0.125 mm in the form of powder and in the form of shale briquette was subjected to heat treatment. The change in the total porosity was studied in the temperature range (0÷1000) oC. The change in the total surface area of nanopores was studied by comparing the initial sample of oil shale with the oil shale ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Методология. Характеристики полученного топлива с добавками исследовали на соответствие требованиям ГОСТ Р 52368 [36]. Определение группового углеводородного состава представительных образцов дизельного топлива (ДТ) и дизельного топлива с добавкой проведено на газовом хромато-масс-спектрометре GCMS-QP2010 SE Shimadzu.…”
unclassified
“…Методология. Характеристики полученного топлива с добавками исследовали на соответствие требованиям ГОСТ Р 52368 [36]. Определение группового углеводородного состава представительных образцов дизельного топлива (ДТ) и дизельного топлива с добавкой проведено на газовом хромато-масс-спектрометре GCMS-QP2010 SE Shimadzu.…”
unclassified
“…After 40 min of settling time, the spectrometric analysis showed that the turbidity of the clarified water was 278 mg/dm 3 ; thus, the recycled water was purified to a level of 95% (Figure 6). The study of a calcium-aluminum-silicate reagent effect on clay minerals was carried out using a TESCAN Vega electron scanning microscope with a field emission cathode at an accelerating voltage of 20 kV in secondary electron detection mode [25]. The sample of the condensed sediment was dried at room temperature and attached to the holder with conductive carbon tape (Figure 7).…”
Section: Synthesis Of Inorganic Precipitantmentioning
confidence: 99%